2019
DOI: 10.18488/journal.31.2019.61.93.108
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent and Consequences of Risk Perception on Tourist Decision Making towards the Sustainable Medical Tourism Development in Bangladesh

Abstract: Contribution/Originality: This study is one of the very few studies which have investigated the relationship between tourist experience, tourist attitude and medical influence on risk perception towards tourist decision making for the sustainable development of medical tourism through empirical analysis and analyses whether tourist become satisfied through risk perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
1
15
1
6
Order By: Relevance
“…Several studies on tourist behavior have found that some individual characteristics may affect travel intentions. Variables such as age (Hajibaba et al, 2015 ; Khan et al, 2018 ; Neuburger & Egger, 2020 ), travel experience (Kozak et al, 2007 ; Polas et al, 2019 ; Sönmez & Graefe, 1998a ), income (Sönmez & Graefe, 1998b ; Floyd et al, 2004 ; Djeri et al, 2014 ; Li et al, 2018 ), and education level (Qi et al, 2009 ; Sönmez & Graefe, 1998b ) were relevant predictors of travel intentions also during periods of crises.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on tourist behavior have found that some individual characteristics may affect travel intentions. Variables such as age (Hajibaba et al, 2015 ; Khan et al, 2018 ; Neuburger & Egger, 2020 ), travel experience (Kozak et al, 2007 ; Polas et al, 2019 ; Sönmez & Graefe, 1998a ), income (Sönmez & Graefe, 1998b ; Floyd et al, 2004 ; Djeri et al, 2014 ; Li et al, 2018 ), and education level (Qi et al, 2009 ; Sönmez & Graefe, 1998b ) were relevant predictors of travel intentions also during periods of crises.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous studies have shown that more internationally experienced tourists tend to have stronger intentions of traveling during periods of crisis (Floyd et al, 2004 ; Pennington-Gray et al, 2011 ; Rittichainuwat & Chakraborty, 2009 ; Sönmez & Graefe, 1998b ). Travel experience decreases tourist risk perception and, at the same time, positively influences travel intentions (Kozak et al, 2007 ; Neuburger & Egger, 2020 ; Polas et al, 2019 ; Rittichainuwat & Chakraborty, 2009 ; Sönmez & Graefe, 1998a ). In a similar vein, past travel experience seems to provide a greater sense of safety to tourists (Reza & Samiei, 2012 ) and alters travel decisions more than information from external sources (Rittichainuwat & Chakraborty, 2009 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Peattie et al ( 2005 ), defined tourist health risk as the probability of suffering from diseases or other health complexities due to the exposure to any traveling experiences. The existing literature on tourism posited travel as a complex process innately containing a significant level of uncertainties and risks that make the tourism sector highly vulnerable (Bhattacharjee et al, 2018 ; Fuchs et al, 2013 ; Polas et al, 2019 ; Williams & Baláž, 2015 ). Jonas et al ( 2011 ) identified tourist health risk as an inseparable part of traveling which has endangering impact on the safety and security of the tourists that enhances their hesitation to travel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some suggest that a high perceived risk increases the hustle and bustle of visitors and impacts hesitation toward tourism decision-making (Beneke et al, 2013 ; Mason et al, 2016 ; Russell-Bennett et al, 2005 ). Furthermore, the fundamentals of tourist decision-making and travel behavior are thoroughly studied, but there has been a lack of studies incorporating the issue of tourist hesitation due to tourist insufficient perception and knowledge (Jonas & Mansfeld, 2017 ; Lalicic & Önder, 2018 ; Peng & Chen, 2019 ; Polas et al, 2019 ). Wong and Yeh ( 2009 ) investigated the relationship of tourist hesitation with destination decision-making and found evidence of tourists’ perceived risk positively influencing the tourist hesitation.…”
Section: Introductionmentioning
confidence: 99%
“…Of course another important factor is the tourist point of view and his experience (Perkumien_ e et al 2019). This was analyzed by Polas et al (2019) in Bangladesh, but it has to be said that the factors influencing the decision-making process are the same as in other forms of tourism, including safety. However, the sense of safety is a crucial factor: many medical tourism researchers have expressed concern about the potential negative effects on the safety of medical tourists, the healthcare systemin the host country and in the country of permanent residence of the patientand for global fair access to healthcare as part of the concept of sustainable development (e.g., Horowitz and Rosensweig 2007;Lunt et al 2012;Snyder et al 2012).…”
Section: Medical Tourism In the Concept Of Sustainable Developmentmentioning
confidence: 99%